Поділ слябів сіткою при рішенні двомірної задачі нестаціонарної теплопровідності явним кінцево-від'ємним методом - Тришевський, Олег Ігорович; Салтавець, Микола Вільямович (НТУ "ХПІ", 2015)
Встановлено, що для чисельного рішення теплофізичних задач теплообміну системи валок – полоса, що описуються рівняннями нестаціонарної теплопровідності, найбільш ефективним є метод кінцевих від'ємностей. Для подальшого чисельного рішення задач нестаціонарної теплопровідності (теплового стану) полоси та валків при гарячої прокатці сляби, які э заготовкою при гарячої прокатці листа, поділені умовною сіткою, для можливих варіантів вузлів якої при рішенні двомірної задачі нестаціонарної теплопровідності складені рівняння балансу енергії з подальшою кінцево-від'ємною апроксимацією Фурье.

It is set that for the numeral decision of thermophysical tasks of heat exchange of the system roller-stripe, which are described equalizations of nonstationary heat conductivity, most effective is a method of eventual differences. For the further decision of tasks of non-stationary heat conductivity (thermal state) of stripe and rollers at the hot rolling slabs, being a purveyance at the hot rolling of sheet, divide a conditional net, for the possible variants of knots of that at the decision of two-dimensional task of non-stationary heat conductivity worked out equations of balance of energy with further eventual difference approximation of Fourier. The got materials of researches can serve as basis for the further numeral decision of tasks of nonstationary heat conductivity (thermal state) of stripe and rollers at the hot rolling.
Decision of tasks of non-stationary heat conductivity by an obvious eventual difference method with the use of division of slabs by a conditional net
Keywords: сляб; гаряча прокатка; ділильна сітка; тепловий стан; нестаціонарна теплопровідність; баланс енергії; апроксимація; кінцево-від'ємний метод; slab; sheet; hot rolling; thermal state; non-stationary heat conductivity; balance of energy; approximation; eventual difference method